The Impact of Farmer’s Participatory Interventions in Improving the Productivity and Income from Cashew in the Indian West Coast - Mangalassery, S.; Muralidhara, B. M.; Nayak, M. G.; Preethi, P.; Adiga, J. D. (Annals of Arid Zone, 2022)
The participatory extension approaches in the dissemination of agro-techniquesserve as an important strategy in reaching the technologies to the clients. Farmer’sparticipatory extension was carried out in cashew plantations in coastal India todemonstrate the usefulness of scientific management practices of nutrient management.The preliminary survey showed that 65% of the farmers did not apply manure andchemical fertilizers. The rest of the selected farmers applied only less than half of therecommended fertilizers, mainly nitrogenous fertilizers or NPK mixture. Only 23% offields received a minimal quantity of manures. About 12% of fields received the integratedapplication of manures and fertilizers. Organic carbon status was low to medium inthe selected fields and among major nutrients, nitrogen was the most limiting nutrient,followed by potassium. Micronutrient deficiencies of zinc, boron and molybdenumwere also observed. The adoption of scientific nutrient management practices alongwith other agro-techniques for two years found to increase the soil pH. The organiccarbon content was improved by 7% and available nitrogen by 9.7%, soil phosphorusand potassium by 6.6 and 15.8% respectively by the adoption of scientific managementpractices. Among the micronutrients in soil, the copper content was increased by 19%.The adoption of scientific nutrient management practices as per the soil test and leafnutrient status was beneficial to improve the nutrient uptake by the plants as observedfrom the increased leaf nutrient status of all essential nutrients. The beneficial effectsof the technologies on improving the yield, net returns and the benefit-cost ratio wereexperienced by the growers.